Assessing available information on the burden of sepsis: global estimates of incidence,prevalence and mortality - Issrah Jawad; Ivana Lukšić; Snorri Bjorn Rafnsson (Edinburgh University Global Health Society, 2012)
Sepsis is a complex and hard-to-define condition with many different interactions with other disorders. Presently, there are no estimates of the burden of sepsis and septicaemia at the global level and it was not included in the initial Global Burden of Disease study. Non-maternal sepsis has only recently received attention as a substantial global public health problem. The aim of this study was to assess available data on the burden of non-maternal sepsis, severe sepsis and septic shock in the community and to identify key gaps in information needed to estimate the global burden of sepsis.